NON-STATE SUBJECTS IN POLICE ACTIVITIES - Matvejevs, Aleksandrs (Administrative and Criminal Justice, 2018)
In this article, the author considers the non-state subjects of the police activity. In the article sums the position theoretical inclusion of civil structures in the law-enforcement system taking into account modern tendencies of development of relations in the Republic of Latvia, namely: the state policy of development and support of the institutions of civil society. Police activities are carried out by various actors: the police, public organizations, private enterprises, individual citizens. Together, they form a system of subjects of police activity, defining the place in which the police bodies occupy themselves as special executive bodies.